Dynamics of River Channel and Land Degradation in Majuli Island: A Geomorphological Perspective - Kamal Das,; Dr. C.K. Dutta,; Koustov Jyoti Hazarika,; Susmita Roy Karmakar, (The Bioscan, 2025)
River channels exhibit a complex interplay of spatial and temporal characteristics influenced by various factors, including geological formations and river dynamics. Majuli, the world's largest river island spanning 352 square kilometers, showcases a unique landscape shaped by periodic flooding and progressive changes. This study investigates the evolution of river channels and land degradation in Majuli Island from 1973 to 2021. Utilizing Landsat data spanning nine consecutive years, spatial analyses were conducted using ArcGIS 10.3 to assess channel migration, channel cross-profile changes, alterations in channel patterns, physical boundary patterns; land use and land cover (LULC) changes, and land degradation trends. The integration of temporal and spatial analyses facilitated the detection of shifts in channel morphology and land degradation patterns across the island. The findings reveal a substantial land degradation of approximately 81.56 square kilometers over the study period, attributed to channel migration and alterations in channel patterns influenced by the geological characteristics of Majuli and the dynamics of the Brahmaputra River. Spatial analysis highlights the necessity for mitigation measures, particularly in the southern and western regions of Majuli, to address the identified vulnerabilities.